Cow–calf performance, forage utilization, and economics of warm-season annual baleage in beef cattle winter feeding systems. Issue 1 (9th November 2019) - Panhans, Mekenzie H; Mason, Katie M; Mullenix, Mary K; Prevatt, Chris G; Moisá, Sonia J; Muntifering, Russell B
Abstract: A 52-d winter feeding trial was conducted to determine animal performance, utilization, and economics of pearl millet (PM) baleage, sorghum × sudangrass (SS) baleage, and "Tifton 85" bermudagrass (B) hay for lactating beef cow–calf pairs. Cone (C) and open-shaped (O) rings were evaluated for potential to minimize forage wastage. The experiment was a completely randomized design with a 3 × 2 factorial arrangement of treatments for each forage type × hay ring (3 cow–calf pairs per treatment; 2 replications per treatment). Animal response measures included cow body weight (BW) change and body condition score (BCS) over the 52-d trial, initial and final calf BW, and cow milk production at the midpoint and end of the study. Forage nutritive value parameters evaluated for each forage type included ash, crude protein (CP), in vitro true digestibility (IVTD), neutral detergent fiber (NDF), acid detergent fiber, and acid detergent lignin (ADL). Forage wastage was estimated for each forage × ring treatment as the percentage of the bale weight remaining in feeding rings at the time of bale replacement. An economic evaluation of the relative costs associated with production and utilization of each forage type was calculated. There were no differences ( P ≥ 0.10) in cow BW change or BCS change among forage types, between ring shapes, or an interaction observed for these response variables. Proportion of waste from PM and SS baleage was greater ( P < 0.10) than for B hay, although there was no forage type × hay ring interaction or differences between O and C hay ring treatments for forage waste ( P ≥ 0.10, respectively). Cow milk production and calf BW gain did not differ among forage type ( P ≥ 0.10, respectively); however, beef calves in pens containing the O ring feeder weighed 6 kg more ( P ≤ 0.05) than calves whose dams were fed using C rings. The economic analysis implies that it is more costly to feed warm-season annual forage baleage to cow–calf pairs than dry hay, largely due to greater costs of production, lack of difference in animal performance responses, and less utilization of baleage compared with feeding bermudagrass hay in this trial.